Indications for Pediatric Enucleations of Non-Retinoblastoma Globes in Saudi Arabia with Clinical and Radiological Correlation To Final Histopathological Diagnosis - Azza MY. Maktabi; Hala A. Helmi; Yaser M. Benthabet; Seham Aljohar; Hind Manaa Alkatan (Journal of Epidemiology and Global Health)
Abstract Background Enucleation is a difficult surgical decision in the ophthalmic practice. The overall commonest indications for this procedure are intraocular neoplasm (mostly retinoblastoma in children and uveal melanoma in adults), trauma, painful blind eyes, phthisis bulbi, and microphthalmos for cosmetic restoration of the orbital size. Specific indications vary according to age groups, gender, and geographical areas. In this study we aim to investigate the indications -other than retinoblastoma- for enucleation in the pediatric age group to observe the trends and significant associations of these indications with our demographic and social background. Methods A retrospective cohort study of non-retinoblastoma globes based on histopathological examination obtained from pediatric patients younger than 18 years of age in a tertiary eye hospital over the period 2000 to 2021. Descriptive analysis was used as well as comparative analysis to highlight the differences between clinical, radiological, and final histopathological diagnoses and to correlate different ophthalmic indications to age and gender. We also investigated the accuracy of clinical and radiological evaluation with special attention to the misdiagnosis of retinoblastoma. Results A total of 47 enucleated globes from 47 patients were included in the study with the majority being in the younger age group of three years or less (40.4%). Males constituted 57.4% of the cohort and the remaining 42.6% were females. Ruptured globe was the main clinical indication in about half of the enucleations followed by painful blind or phthisical eyes. Traumatic enucleations were significantly associated with older age group of 7 years or older (p = < 0.001). Interestingly, four globes and three globes were mis-diagnosed as retinoblastoma clinically and radiologically respectively and were accurately diagnosed after histopathological examination of the enucleated globes. Conclusion Eye trauma is a leading cause for pediatric enucleation in about half of the non-retinoblastoma globes with higher prevalence in older children. When combined with end stage traumatized globes presenting as painful blind eye or phthisis bulbi, the rate increases to 57.4% of the enucleations. Health awareness and safety measures during sports and other activities should be implemented. Ophthalmologists should be aware of ophthalmic diseases presenting as pseudoretinoblastoma leading to possible unnecessary enucleations.